AVERAGE DAILY CONSUMPTION OF FOODS AND OF FOODS ACCUMULATING LEAD AND CADMIUM IN YOUNG PEOPLE - Vanya Birdanova; Irena Stoilova; Ivelina Ruseva; Zdravka Radionova (Peytchinski Publishing, 2023)
Purpose of the study is to investigate food consumption in young people and the contribution of food to heavy metal pollution. Methods: The object of the study are 60 healthy young people aged 19-29 years (average age - 23,9 ± 2,6) from Pleven and the Pleven district. Assessment of food intake was made according to A two-day, 24-hour diet recall method and Food Frequency Questionnaire (FFQ) method. A documentary method was used to assess the content of heavy metals- data provided by the Food Chain Risk Assessment Centre Data provided by the Food Chain Risk Assessment Centre. 2,471 food samples were analyzed for lead and cadmium over a 7-year period. Result: The food group importing complex carbohydrates could have a probable contribution to the dietary exposure to Pb and Cd, as they are consumed in the recommended amounts, although no content of lead and cadmium above the maximum permissible amounts was found in the studied foods. Intake of vegetables and fruits is significantly below recommended - vegetables and fruits would likely contribute to dietary exposure to Pb and Cd provided they were consumed as recommended. The average daily intake of dairy products is compared to the references. Game meat and offal could contribute to dietary exposure to both heavy metals, but these were also not consumed by the respondents. Fish and seafood likely contribute to dietary exposure to heavy metals, but their consumption is low and significantly below recommendations. Conclusion: The obtained results confirm the importance of a healthy food model for the protection of human health, including protection from chemical hazards in food.